Regenerative Agents: Patient‐Focused Architectures. (March 2017) - Prasad, Sunand
Abstract : Holistic care is nothing new. There are well‐known examples across the world and throughout history – from ancient Greece, China and India to early 20th‐century northern Europe – of approaches that prioritise placemaking as a facilitator for health and healing. Inspired by such precedents, London‐based architects Penoyre & Prasad produce buildings that engage with nature and help put patients back in control of their recovery process.Sunand Prasad, one of the firm's cofounders, explains.